KNOWLEDGE, ATTITUDE, AND PRACTICE OF BASIC LIFE SUPPORT AMONG NURSING STUDENTS IN THE COLLEGE OF NURSING NISHTER MEDICAL UNIVERSITY/HOSPITAL MULTAN - RASHID , SA; MAJEED, S; RUBAB, M; YASMIN, R (Biological and Clinical Sciences Research Journal, 2024)
Basic Life Support (BLS) is a critical skill for healthcare providers, enabling them to respond effectively to cardiac and respiratory emergencies. However, limited training and resource constraints pose challenges to BLS knowledge, attitudes, and practices (KAP) among nursing students in Pakistan. Objective: To evaluate the knowledge, attitudes, and practices of BLS among nursing students at Nishtar Medical University, Multan, and identify gaps that could inform curriculum enhancements. Methods: A descriptive cross-sectional study was conducted among 130 nursing students from all academic years. Data were collected using a structured questionnaire based on international BLS guidelines, assessing demographic characteristics, knowledge, attitudes, and practices. Statistical analysis was performed using SPSS version 26, employing descriptive and inferential statistics. A p-value ≤0.05 was considered significant. Results: Among the participants, 84.6% correctly identified the abbreviation of BLS, and 73.1% knew the correct chest compression location. However, only 53.8% demonstrated competence in performing CPR in simulated scenarios. Positive attitudes toward BLS training were prevalent, with 96.2% advocating for its inclusion in the nursing curriculum and 88.5% willing to undergo hands-on training. Prior BLS training significantly correlated with higher knowledge and practice scores (p<0.05).Conclusion: While nursing students at Nishtar Medical University exhibit adequate theoretical knowledge and positive attitudes toward BLS, practical proficiency remains suboptimal. Integrating hands-on BLS training into the curriculum and addressing resource limitations is essential to enhance emergency response capabilities and reduce preventable mortality.